HOMESCHOOLING; PENDIDIKAN ALTERNATIF DI INDONESIA - Zul Afiat (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2019)
This article aims to examine the theoretical concept, classification, models, supporting factor, types of homeschooling and the implementation of homeschooling in Indonesia. The discussion of homeschooling was in the perspective of child development. The conclusion based on the theoretical concept describes that it was an educational form which was done independently by family, and the learning materials were choosen in accordance with the children need. The homeschooling classification forms was divided into two forms namely single home schooling which was conducted independently by parents in one family withought collaborating with aothers.Compound homeschooling was conducted by two or more families for certain activities, but the main activities remain to be implemented by the respective parents. Homeschooling was an education for the children who performed at home and was specifically provided by a parent or a professional tutor. Homeschooling in practice was to move the school from the public area to a more private area, which was home. Abstrak Tulisan ini bertujuan untuk mengkaji konsep teoritik, klasifikasi, model, faktor-faktor pendukung, jenis homeschooling dan pelaksanaan homeschooling di Indonesia. Pembahasan Homeschooling ini adalah dalam perspektif perkembangan anak. Kesimpulan hasil kajian secara teoritik adalah bahwa Homeschooling adalah pendidikan yang dilakukan secara mandiri oleh keluarga, yang materi pembelajarannya dipilih dan disesuaikan dengan kebutuhan anak. Klasifikasi format homeschooling terbagi dua yaitu homeschooling tunggal yang dilaksanakan oleh orangtua dalam satu keluarga tanpa bergabung dengan lainnya, dan homeschooling majemuk dilaksanakan oleh dua atau lebih keluarga untuk kegiatan tertentu sementara kegiatan pokok tetap dilaksanakan oleh orangtua masing-masing. Homeschooling merupakan pendidikan bagi anak-anak yang dilaksanakan di rumah dan secara khusus diberikan oleh orang tua atau seorang tutor profesional. Homeschooling dalam praktiknya memindahkan sekolah dari area umum ke area yang lebih privat, yakni ke rumah. Kata Kunci: Home schooling, Pendidikan Alternatif